Amylin, Aβ42, and Amyloid in Varicella Zoster Virus Vasculopathy Cerebrospinal Fluid and Infected Vascular Cells. (18th August 2020) - Bubak, Andrew N; Beseler, Cheryl; Como, Christina N; Coughlan, Christina M; Johnson, Noah R; Hassell, James E; Burnet, Anna M; Mescher, Teresa; Schmid, D Scott; Coleman, Colin; Mahalingam, Ravi; Cohrs, Randall J; et al.
Abstract: Background: Varicella zoster virus (VZV) vasculopathy is characterized by persistent arterial inflammation leading to stroke. Studies show that VZV induces amyloid formation that may aggravate vasculitis. Thus, we determined if VZV central nervous system infection produces amyloid. Methods: Aβ peptides, amylin, and amyloid were measured in cerebrospinal fluid (CSF) from 16 VZV vasculopathy subjects and 36 stroke controls. To determine if infection induced amyloid deposition, mock- and VZV-infected quiescent primary human perineurial cells (qHPNCs), present in vasculature, were analyzed for intracellular amyloidogenic transcripts/proteins and amyloid. Supernatants were assayed for amyloidogenic peptides and ability to induce amyloid formation. To determine amylin's function during infection, amylin was knocked down with small interfering RNA and viral complementary DNA (cDNA) was quantitated. Results: Compared to controls, VZV vasculopathy CSF had increased amyloid that positively correlated with amylin and anti-VZV antibody levels; Aβ40 was reduced and Aβ42 unchanged. Intracellular amylin, Aβ42, and amyloid were seen only in VZV-infected qHPNCs. VZV-infected supernatant formed amyloid fibrils following addition of amyloidogenic peptides. Amylin knockdown decreased viral cDNA. Conclusions: VZV infection increased levels of amyloidogenic peptides and amyloid in CSF and qHPNCs, indicating that VZV-induced amyloid deposition may contribute to persistent arterial inflammation in VZV vasculopathy. In addition, we identified a novel proviral function of amylin. Abstract : Varicella zoster virus (VZV) vasculopathy cerebrospinal fluid and VZV-infected perineurial cells were examined and found to contain significantly increased amyloidogenic peptides and amyloid. The presence of proinflammatory and cytotoxic amyloid in VZV vasculopathy suggests it may contribute to vasculitis pathogenesis.